Risky Lives? Self-Directed Violence and Violence From Others Among Young People Not in Education, Employment, or Training (NEET) - Haugland, Siri Havas; Stea, Tonje Holte (Frontiers in Public Health, 2022)
Self-directed violence and violence from others comprise a major public health concern in youth. However, we lack knowledge about the prevalence of violent experiences among young people that are not in education, employment, or training (NEET), whether violent occurrences are similar among girls and boys, and whether violence differs between NEET youths and young students. This cross-sectional study compared the occurrences of self-directed violence (suicide attempts and self-harm) and exposure to violence from others (violent threats, beaten without visible marks, or injured due to violent events) between 96 NEET youth and 384 age- and sex-matched upper secondary school students (16-21 years). Suicide attempts were reported by 45.2% of NEET girls and 18.8% of schoolgirls (p<.001), but no significant difference was found between NEET boys (17.6%) and schoolboys (13.1%). Self-harm was reported by 78.9% of NEET girls and 33.9% of schoolgirls (p<.001). Self-harm was less prevalent among boys; it was reported by 34.6% of NEET boys and 21.8% of schoolboys (p=.056). A multivariable logistic regression analysis, adjusted for parental education, showed that, compared to schoolgirls, NEET girls had much higher odds ratios (ORs) for both self-directed violence and violence from others with OR ranging from 4.39; CI 1.96-9.85 to 7.68; CI 3.20-18.41. The risk of injury due to violent events was higher among NEET boys (OR: 3.23, 95%CI: 1.21-8.62) compared to schoolboys. Our findings highlighted the importance of including NEET individuals in studies on violence and emphasized the importance of psychosocial health services for young people marginalized from education and the labor market.